Analisis Kemampuan Komunikasi Matematika Siswa Ditinjau dari Gender - urni babys (Universitas Muria Kudus, 2020)
The purpose of this study is to describe the mathematical communication ability of students in terms of gender. This type of research is a descriptive study with a quantitative approach. This research was conducted at Soe Middle School 3 2018/2019 school year. The source of data in this study were 20 VIII 10 students, consisting of 10 men and 10 women. Sampling using simple random sampling technique. The data collection technique used is a test of mathematical communication skills. The research procedure goes through several stages, namely: 1) preparation of mathematics communication skills test questions, 2) validating test questions and results analysis, 3) providing tests and collecting test results, 4) analyzing test results, 5) drawing conclusions. From the results, the communication skills of female students on all indicators have a higher value than male students. Female students are more thorough, careful and patient in solving mathematical problems so they are able to communicate mathematical ideas with pictures, diagrams or symbols and have a better mathematical representation than male students of the study. It can be concluded that the mathematical communication ability of female students is higher than the mathematical communication ability of male students that is equal to 58.71% or a difference of 17.42%